STUDY ON THE EFFECT OF THE COMPOUND SBVN TOWARD THE EXPRESSION - Thảo, Đỗ Thị (Vietnam Journal of Biotechnology, 2011)
The Oct4 gene plays an important role in the developmental and differentiated process of stem cells. Recently, several scientific studies noted that the Oct4 gene expressed not only in embryonic stem cells but also in the carcinogenic cells. However, knowledge about the real role and action mode of the Oct4 toward carcinogenesis remains poorly. In this study, we evaluated the effect of the novel anticancer promising compound - Scutebarbalactone VN (SBVN) on the expression of the Oct4 gene using in vitro cultured P3XAgl8 cancer cells. SBVN were obtained by bioassay-guided fractionation and isolation from the methanol exfract ofthe Vietnamese medicinal plant Ban-chi-lien (Scutellaria barbata D. Don). The bioassays were used such as cytotoxic assay, aromatase inhibition assay, C0X2 inhibition assay etc. By using Real-Time PCT techniques for relatively quantification, we studied the effect of SBVN toward the action of Oct4. The results showed that SBVN inhibited the expression of Oct4 while it did not effect to the action of P-tubulin - the house keeping gene.